Ethnomathematics: Learning Geometric Transformation Through the Formation of Lagosi Motif - Hikmawati Pathuddin; Zulfiqar Busrah (Jurnal VARIDIKA, 2024)
The Lagosi motif, a prominent design in the traditional fabric of the Wajo district, is well-known but increasingly rare among local weavers. This motif, drawing inspiration from natural elements such as flowers and stems, holds significant philosophical and cultural meaning for the Wajo people, serving as a key element of their endangered cultural heritage. Despite its cultural importance, the motif has been minimally explored in the context of ethnomathematics. Consequently, this study investigates the mathematical concepts inherent in the design of Lagosi motifs, aiming to utilize them as educational tools for students and to support cultural preservation efforts. Employing a qualitative research methodology with an ethnographic approach, data were collected through observations, interviews, and documentation. The validity and reliability of the data were ensured through triangulation and confirmability. The study reveals that geometric transformations, specifically translation and reflection, play a central role in the creation of Lagosi motifs. These findings highlight the natural emergence of mathematical concepts within local cultural practices, offering potential for their integration into contextualized mathematics education. Furthermore, the results aim to instill a sense of cultural pride in students, thereby contributing to the preservation of Wajo's cultural heritage. The study also underscores the opportunity to leverage Lagosi motifs as culturally relevant educational tools and to foster interdisciplinary collaboration between mathematics and cultural studies.